A Comparative Study of the Sound Systems Used by Sound Horeg Rajawali Audio and JL Music at the Artes Squad Anniversary Festival in Jombang - Ahmad Nur Azizul Hakim (Universitas Negeri Surabaya, 2026)
This study aims to compare the sound systems used by Rajawali Audio and JL Musik at the Artes Squad Anniversary Festival. The process began with a description of the sound system setups, followed by an analysis of the results by both vendors. The data in this qualitative case study were analyzed by following a cycle of data collection, reduction, and verification of findings to arrive at accurate conclusions. Based on the analysis, it can be concluded that, in terms of technical sound setup, both vendors took a similar approach. The absence of an input source was the main distinguishing factor for JL Musik. Regarding audio quality, Rajawali Audio excelled at producing powerful low frequencies for maximum “horeg” effects. Meanwhile, JL Musik prioritizes clarity and midrange balance, though its subwoofer performance does not yet match Rajawali Audio's intensity.